НАУКОВИЙ ФАКТ ЯК МЕТОДОЛОГІЧНА КАТЕГОРІЯ У ШКІЛЬНОМУ КУРСІ БІОЛОГІЇ (Педагогіка вищої та середньої школи, 2022)
In the article is described classification o f biological facts, which are available in the school biological education, and given an examples of educational tasks for the seventh form. On the basis of it the conclusion about necessity of allocation for separate group of the facts of historical-metodological character and development of a methodic of their use in practice of instructing of biology is made